Cidade, inconsciente e poesia : uma triangulação na obra de Roberto Piva - Brito, Rodrigo Fernandes Ferreira (2023)
The present thesis aims to discuss the triangulation between city, unconscious and poetry in Paranoia (1963), by Roberto Piva and Duke Lee, and Piazzas (1964), a work by Roberto Piva. The need to reflect on modernity and its unfoldings for psychic and urban life is revealed. From the connection of the triangle of Piva with modernity, the contributions of Freud (2010, 2010, 2015, 2015, 2016 and 2016), Lacan (1990 and 1998) and Dunker (2015) are necessary for thematic deepening in dialogue with the contextual particularities of São Paulo of the 1960s. In the first chapter of the thesis, the analysis focuses on the poems "Visions 1961" (PIVA; DUKE LEE, 2009) and "Piazzas I" (PIVA, 1980). At the beginning, the poems are presented in their entirety and during the interpretation the studied verses are appreciated in close reading to privilege the aesthetic and psychic effects of the reading. The fact that the lyric self is a wanderer in São Paulo builds metaphors of the city, which in its alleys, galleries, and Aurora and Rio Branco streets constitutes the presence of modernity, which has repercussions in social facts and in the unconscious. In the second chapter, Duke Lee's photographs lead to an analysis of triangulation, in which the connection between photographic language and psychoanalytic investigation is essential. The chapter is divided into two sections for the understanding about the gaze and memory. In both, the unconscious will be the main point of reflection, but still privileging the other points of the triangle: poetry and the city. Although there is the choice of starting the interpretative path focusing on the unconscious, the thesis also seeks theoretical subsidies in Aumont (1993), Dubois (1998), Sontag (1994) and Barthes (1994) to scrutinize new meanings based on literary studies and photographic language.